"Are You Only an Applauder?" American Music Correspondence Schools in the Early Twentieth Century. (January 2015) - Vogel, Dorothy
The purpose of this study was to examine correspondence schools of music in the early twentieth century. Advertisements in widely circulated household and music periodicals and archival copies of courses from Siegel-Myers Correspondence School of Music, United States School of Music, American College of Music, and others were examined. Research questions focused on course offerings, faculty, recruitment, and reputation of the schools. The study also examined the advantages and disadvantages of this first generation of distance education and implications for current distance education practices today. Results revealed that correspondence schools of music had more breadth and, in some cases, depth than previous research had indicated. Instruction at numerous schools was offered on a wide variety of instruments, including voice, as well as in music history, music theory, and music teacher education. One of the prominent teacher education resources was Frances Elliott Clark's Course in Public School Music offered through Siegel-Myers Correspondence School of Music. Instruction reached a wide demographic, including segments of the population without alternate access to music education. This rich history shows that distance education has been and will remain a viable and valuable option for accessing music education.